Does a joint development and dissemination of multidisciplinary guidelines improve prescribing behaviour: a pre/post study with concurrent control group and a randomised trial - Winkens Ron AG; Martens Jody D; van der Weijden Trudy; de Bruyn Daisy; Severens Johan L (BMC, 2006)
Abstract Background It is difficult to keep control over prescribing behaviour in general practices. The purpose of this study was to assess the effects of a dissemination strategy of multidisciplinary guidelines on the volume of drug prescribing. Methods The study included two designs, a quasi-experimental pre/post study with concurrent control group and a random sample of GPs within the intervention group. The intervention area with 53 GPs was compared with a control group of 54 randomly selected GPs in the south and centre of the Netherlands. Additionally, a randomisation was executed in the intervention group to create two arms with 27 GPs who were more intensively involved in the development of the guideline and 26 GPs in the control group. A multidisciplinary committee developed prescription guidelines. Subsequently these guidelines were disseminated to all GPs in the intervention region. Additional effects were studied in the subgroup trial in which GPs were invited to be more intensively involved in the guideline development procedure. The guidelines contained 14 recommendations on antibiotics, asthma/COPD drugs and cholesterol drugs The main outcome measures were prescription data of a three-year period (one year before and 2 years after guideline dissemination) and proportion of change according to recommendations. Results Significant short-term improvements were seen for one recommendation: mupirocin. Long-term changes were found for cholesterol drug prescriptions. No additional changes were seen for the randomised controlled study in the subgroup. GPs did not take up the invitation for involvement. Conclusion Disseminating multidisciplinary guidelines that were developed within a region, has no clear effect on prescribing behaviour even though GPs and specialists were involved more intensively in their development. Apparently, more effort is needed to bring about change.